A Narrative Study of the Older Patient and Family Caregiver Experience of Alternate Level of Care - Cressman, Greg (My University, 2011)
Alternate Level of Care, or ALC, is a designation assigned to a patient during an acute care hospital stay when that patient is occupying a bed but no longer requires that intensity of service. A high proportion of beds occupied by patients requiring ALC results in problems in the healthcare system related to patient flow, access, and efficiency. The purpose of this study was to better understand the experience of older patients and family caregivers while the patient is designated as requiring ALC. This study employed the Three-Dimensional Narrative Inquiry Space method of Clandinin and Connelly (2000) to examine the experiences of five patients and four family caregivers. The primary data source for this study was a series of semi-structured interviews with individual participants over time while they were in the midst of the experience of ALC. Data analysis involved a twofold process of restorying all interview transcriptions for a given participant into a single story summarizing his or her experience, and analyzing the content across stories to identify common themes. The major finding of this study was that uncertainty was a significant part of the experience of ALC. This uncertainty was manifest in relation to self-concept, waiting for placement, not knowing about information, not being included in planning, lack of mobility, and lack of meaningful activity. The study findings have implications for strategies to manage uncertainty in the areas of practice, policy, education, and research in order to improve the experience of older patients and their family caregivers.
Keywords: alternate level of care; narrative research; patient and family experiences; uncertainty; information needs; discharge planning; acute care; Geriatric Nursing; Geriatric Nursing